1995
DOI: 10.1161/01.cir.92.9.2419
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Cardiovascular Events During Pravastatin Therapy

Abstract: These pooled results provide strong evidence that pravastatin reduces the risk of cardiovascular events in patients with atherosclerotic disease and mildly to moderately elevated lipid levels. The benefit for reducing myocardial infarction is evident in older and younger patients, men and women, and patients with and without histories of hypertension and prior infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(63 citation statements)
references
References 19 publications
1
57
1
2
Order By: Relevance
“…Similar reductions in the risk of events such as heart attack or stroke occur with statins and antihypertensive medication. 44 A pooled analyses of three randomised trials comprising 4222 men with moderately symptomatic BPH treated with either finasteride or placebo for 2 y reported 81 episodes of AUR (24/2113 finasteride group, 57/2109 placebo group). 42 The hazard ratio for the occurrence of AUR was consistent among the studies with a 57% decrease in the hazard rate for patients treated with finasteride compared with placebo (Po0.001).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Similar reductions in the risk of events such as heart attack or stroke occur with statins and antihypertensive medication. 44 A pooled analyses of three randomised trials comprising 4222 men with moderately symptomatic BPH treated with either finasteride or placebo for 2 y reported 81 episodes of AUR (24/2113 finasteride group, 57/2109 placebo group). 42 The hazard ratio for the occurrence of AUR was consistent among the studies with a 57% decrease in the hazard rate for patients treated with finasteride compared with placebo (Po0.001).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Moreover, in tensive lipid lowering using HMG-CoA reductase inhibitors is the most effective in terms of inducing plaque regression and reducing the number of clini cal events in men with established CAD and PVD [18,19,25,28,[30][31][32][33][34][35][36][37][38][39][40][41]. Recently, a meta-analysis that pooled data from four studies treating men and women with 10-40 mg per day pravastatin for 2-3 years showed that a decrease in LDL-cholesterol of 28% from baseline was associated with a 62% reduc tion in the combined incidence of non-fatal and fatal myocardial infarction [57]. More aggressive lipid lowering may even improve these benefits [58].…”
Section: L Hmg-coa Reductase Inhibitorsmentioning
confidence: 99%
“…More recently, studies of serial coronary angiograms in men and women have indicated that LDL-C lowering and HDL-C increasing were associated with the arrest of progression of atherosclerosis and reduction in CAD events both in women and in men [11][12][13]. Finally, in the recent Scandinavian Simvastatin Survival Study (4S), women with CAD had the same reduction in coronary events as men, although an effect on mortality (as a result of low numbers of deaths in women) could not be demonstrated [14].…”
Section: Clinical Trials Of Cholesterol Lowering In Womenmentioning
confidence: 99%
“…Certainly in both men and women with established coronary disease, lowering of LDL levels is an essential component of therapy [11][12][13]. As a reflection of that belief, NCEP guidelines suggest that LDL targets for such individuals should be set very low, i.e.…”
Section: Us Guidelines For Cholesterol Interventions In Womenmentioning
confidence: 99%